Current sustainable development practices in the Malaysian construction industry: stakeholders' perspective - Shari, Zalina; Soebarto, Veronica (Universiti Putra Malaysia, 2012)
Economically, Malaysia has one of the fastest growing construction industries in the world; however, the necessary balance between socio-economic and ecological systems – to avoid further environmental damage – has not yet been reached by the industry. The aim of this paper is to explore the extent of sustainable development practices (socially, environmentally and economically) in the Malaysian construction industry. These views were explored through in-depth interviews with thirty stakeholders from various backgrounds of the Malaysian construction industry. The study finds that economic issues have always been the first priorities among stakeholders in any decision-makings for building projects. As such, cost becomes one of the major reasons for the slow progress in implementing environmental-friendly practices in building projects. Socially, there is still a wide gap of knowledge and awareness on sustainability issues among stakeholders, explaining the lack of commitment in achieving social sustainability. For example, post-occupancy evaluation and universal design are far from being 'mainstream' practices within the construction and property sectors. These are some of the findings that highlight the issues to be bridged in practice as well as in any sustainability assessment framework, in order to make sustainability more socially acceptable and integral in the local construction industry.